Model Penyediaan Dan Aksesibilitas Pangan Di Daerah Defisit Pangan Provinsi Riau : Studi Kasus Di Kabupaten Siak - Gevisioner; Shinta Utiya Syah (Jurnal Kebijakan Pembangunan dan Inovasi, 2016)
The availability and accessibility of food, particularly food to households in the area of food deficits such as Riau future, face the challenge of quite serious, because of the high population growth, poverty, the environmental degradation, drought and land use changes will affect the availability of food and the increasing reliance food supplies to meet food deficits Riau Province. This study aims to formulate a model or pattern of provision and accessibility of household food. This research was conducted in Siak with the scope of the research in two districts-districts Mempura and Sei. Mempura.. Each district selected two (2) of the village. The choice of location is based on purposive sampling. The results showed that 1) Model household food supply in Siak district is formed from its own purchasing and production factors; 2) Model household food accessibility in Siak district is formed of factor incomes, rising food prices, the condition of road infrastructure. Realize the provision and accessibility of sustainable food for households in Siak district can be pursued through: 1) Increasing the role of Local Government Siak district in the provision of food reserve regional food reserve communities, 2) Development of empowerment of farmer group in the provision of food communities, 3) Increasing the quantity and the quality of movement diversification of food consumption locally diverse diverse, nutritious, balanced and secure, 4. Development of warning systems for food and nutrition are applicable.